Ghana [In West African agriculture and climate change: A comprehensive analysis] - Nutsukpo, Delali Kofi; Jalloh, Abdulai; Zougmoré, Robert B.; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2013)
Including inland water bodies, Ghana covers 238,539 square kilometers and is located on the south central coast of West Africa. The country shares bor¬ders in the east with Togo, in the north with Burkina Faso, and in the west with Côte d’Ivoire. The topography of Ghana is mainly undulating, with most slopes less than 5 percent and many not exceeding 1 percent. The topography of the high rainforest is, however, mainly strongly rolling. The uplifted edges of the Voltarian basin give rise to narrow plateaus between 300 and 600 meters in elevation (Boateng 1998). Moving from the rainforest zone in the south to the Sahara Desert in the north, rainfall generally decreases and temperature increases. Rainfall is the most important climatic factor influencing vegetation in Ghana. The wettest area is in the extreme southwest, where the rainfall is over 2,000 millimeters per year. In the extreme north, the annual rainfall is less than 1,100 millimeters. The driest area is at the southeastern coastal tip, where the rainfall is about 750 millimeters. Much of the rain falls in intense storms of short duration, especially at the beginning of the season, resulting in heavy runoff and erosion. The annual mean relative humidity is about 80 percent in the south and 44 percent in the north (Dickson and Benneh 1988). The mean monthly temperature for the entire country is 25°C. Although temperatures are uniformly moderate, there are important variations over different parts of the country, reflecting altitude and distance from the sea.